Back in black : an A-list novel - Dean, Zoey. (New York : Little, Brown, 2005)
The Hollywood girls make a getaway to the Palms Casino in Las Vegas where they put to the test the universal pact, whatever happens in Vegas stays in Vegas.
Young Adult
Young Adult
Voice of Youth Advocates (V.O.Y.A.)
Keywords: Casinos -- Juvenile fiction; Las Vegas (Nev.) -- Juvenile fiction; Casinos -- Fiction; Las Vegas (Nev.) -- Fiction; Casinos -- Fiction; Las Vegas (Nev.) -- Fiction